IRRI develops rice seedling transplanter - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
To ease the drudgery of transplanting, the International Rice Research Institute (IRRI) has developed an inexpensive mechanical rice seedling transplanter so that one trained operator can trasplant 1/3 hectare per day using the machine. It takes...